Kurangnya Minat Remaja Dalam Belajar Al-Qur’an Akibat Pengaruh Canggihnya Teknologi Informasi - Isabellapavytha, Valda; Ainin Munawaroh; Munawir (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2023)
This research is a literature study using data sourced from textbooks, journals, observational data, and other sources relevant to the topic to be discussed. The literature study in this study focuses on the lack of interest in adolescents in learning the Qur'an caused by the sophistication of information technology, especially gadgets. The purpose of this research is of course to explore the causal factors and solutions to the problems that are the focus of this research. The results of research through several sources of literature reveal that the causes of the lack of interest in student learning can come from themselves, teachers and parents so that the solution in solving this problem must be faced by several parties concerned. One of the factors causing the problem is that the teacher has not been able to provide learning with a method that is suitable for students' abilities so they tend to get bored. The solution to this problem is that teachers should study more deeply about several methods that can be applied to students.